Association of filial attitude, filial behavior and death literacy: implications for development of death system in Guangdong-Hong Kong-Macao Greater Bay Area of China - Wai I Ng; Sok Leng Che; Xiang Li; Mingxia Zhu (BMC, 2024)
Abstract Background Filial piety, as a major traditional norm in Chinese culture and in Chinese families, affects the attitudes and behaviors of adult children toward their parents and impacts their end-of-life decision-making and the quality of death of their parents. Death literacy is a novel concept aimed at promoting palliative care in the context of public health. Aims To understand attitudes and behaviors related to filial piety and to examine the role of death literacy in filial behaviors toward dying parents among residents in the Guangdong-Hong Kong-Macao Greater Bay Area of China. Methods A cross-sectional online survey that employed the convenient and snowball sampling methods was adopted. Filial Piety Representations at Parents' End of Life Scale and Death Literacy Index were used. Results This study identified a significant gap between the filial piety attitudes and behaviors of Chinese adult children. Gender, caregiving experience and death literacy were predictors of filial behaviors in an end-of-life context. Conclusion Providing truth disclosure support, offering guidance to young adult children and caregivers of terminally ill fathers, and strengthening factual and community knowledge of death are necessary to enhance the reciprocal comfort of both adult children and dying parents in the context of Chinese filiality.